Recycling of Biogas Digestates in Crop Production—Soil and Plant Trace Metal Content and Variability - Dragicevic, Ivan; Sogn, Trine A.; Eich-Greatorex, Susanne (Frontiers in Sustainable Food Systems, 2018)
Production of biogas and utilization of the resulting digestates as fertilizers has been increasing in Europe in the last few decades. Depending on the feedstock used for the anaerobic digestion process, these organic fertilizers may be a source of different pollutants, such as trace metals. When applied to soils, digestates may influence the natural metal content and enhance the release of metals to the environment since they can be rich in different trace metals and are usually rich in dissolved organic matter. This study focused on investigating metal presence, seasonal variability of their soluble forms and crop uptake in a two-year field experiment, using two different biogas digestates as fertilizers. The use of digestates as fertilizers was compared to cattle manure, mineral fertilizer and a control without fertilizer addition, with respect to the presence and distribution of the trace metals Cd, Cu, Zn, Ni, Cr, Mn and Mo, as well as Al in the soil and plant. The results of the study showed that both biogas digestates have caused a 10 to 20 % increase in the total soil concentration of Ni, Cd and Cr compared to control plots without fertilizer addition. Application of biogas digestates had only a minor effect on metal uptake in plants. Overall, the selected application rate of 100 kg/ha of plant available nitrogen has had little effect on plant metal uptake and crop quality and the use of biogas digestates was comparable to the use of animal manure.